种四轮独立驱动电动汽车的协调控制方法 (2018)
本发明公开了种四轮独立驱动电动汽车的协调控制方法，包括步骤：、驾驶员操作参数设置电路模块，输入电动汽车的期望纵向速度和期望横向速度，参数设置电路模块再输出给控制器；二、驾驶员操作方向盘，输入方向盘转角信号，方向盘转角传感器对驾驶员输入的方向盘转角信号进行实时检测，并将检测到的方向盘转角信号输出给控制器；三、控制器对电动汽车的期望纵向速度和期望横向速度，以及方向盘转角信号进行分析处理，得到电动汽车的四个轮胎的侧偏角和中心速度；四、控制器根据电动汽车的四个轮胎的侧偏角和中心速度，输出对电动汽车的控制信号，控制电动汽车行驶。本发明方法步骤简单，设计新颖合理，实现方便，能够实现电动汽车的稳定行驶。 The invention discloses a coordination control method for a four-wheel independent-drive electric automobile. The method includes the steps that firstly, a driver operates a parameter setting circuit module to input the expected longitudinal speed and the expected transverse speed of the electric automobile, and then the parameter setting circuit module outputs the expected longitudinal speed and the expected transverse speed to a controller; secondly, the driver operates a steering wheel and inputs a steering wheel rotating angle signal, and a steering wheel rotating angle sensor is used for detecting the steering wheel rotating angle signal input by the driver in real time and outputting the detected steering whee